2022
DOI: 10.1101/2022.01.10.475668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A pleiotropic chemoreceptor facilitates the functional coupling of pheromone production and perception

Abstract: Optimal mating decisions depend on the robust coupling of signal production and perception because independent changes in either could carry a fitness cost. However, since the perception and production of mating signals are often mediated by different tissues and cell types, the mechanisms that drive and maintain their coupling remain unknown for most animal species. Here, we show that in Drosophila, sensory perception and production of an inhibitory mating pheromone are co-regulated by Gr8a, a member of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 91 publications
(166 reference statements)
0
3
0
Order By: Relevance
“…Recently, a role of Gr64 cluster genes was demonstrated in proteostasis and is crucial for the survival of ribosomal protein mutant epithelial cells in D. melanogaster (Baumgartner et al, 2021). Lastly, a pleiotropic role of GRs has been well documented in case of expression in the fly brain, gastrointestinal tract and reproductive sites (Park and Kwon, 2011; Miyamoto and Amrein, 2013; Vernier et al, 2022). Therefore, it can be hypothesized that Gr64b may not perform a chemosensory role but rather act as a GPCR involved in cellular functions when expressed in ab5B neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a role of Gr64 cluster genes was demonstrated in proteostasis and is crucial for the survival of ribosomal protein mutant epithelial cells in D. melanogaster (Baumgartner et al, 2021). Lastly, a pleiotropic role of GRs has been well documented in case of expression in the fly brain, gastrointestinal tract and reproductive sites (Park and Kwon, 2011; Miyamoto and Amrein, 2013; Vernier et al, 2022). Therefore, it can be hypothesized that Gr64b may not perform a chemosensory role but rather act as a GPCR involved in cellular functions when expressed in ab5B neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 2, 2022. ; https://doi.org/10.1101/2022.06.29.498097 doi: bioRxiv preprint Watanabe et al, 2011;Lee et al, 2012;Freeman and Dahanukar, 2015;Fujii et al, 2015;Dweck and Carlson, 2020;Vernier et al, 2022). The first hint about non-canonical expression of GRs in the antenna of D. melanogaster came in the late 2000s, when two independent studies demonstrated that the perception of CO2 depends on Gr21a and Gr63a co-expressed in the ab1C neuron in the D. melanogaster antenna (Jones et al, 2007;Kwon et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation